Sarana Dan Prasarana (Fasilitas) Pendidikan Bagi Anak-Anak Berkebutuhan Khusus - Opi Andriani; Debi Arian Saputra; Kevin Tifani Sulistyo; Linda Nurfitria Sari (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2024)
This research discusses educational facilities for children with special needs. Children with special needs are a group that requires special attention in education. They have different needs in accessing and participating in the learning process. In this article, we explore the importance of adequate educational facilities for children with special needs. Important aspects of such facilities include an adapted physical environment, technological support, the role of teachers and educational staff, as well as the benefits that children with special needs obtain from good educational facilities. The research method used is a descriptive qualitative research method where data collection is carried out by searching for articles from electronic journals, namely Google Scholar (Scholar), which can strengthen the results of the analysis. The data analysis technique in this research includes three stages, namely organize, synthesize and identify. The research results show that facilities for children with special needs have their own functions. Each facility provides its own benefits for children's growth and development. In this way, children with special needs receive maximum service.